A new window into the molecular physiology of membrane proteins. (1st December 2014) - Landreh, Michael; Robinson, Carol V.
<x xml:space="preserve">Abstract</x> Abstract Integral membrane proteins comprise ∼25% of the human proteome. Yet, our understanding of their molecular physiology is still in its infancy. This can be attributed to two factors: the experimental challenges that arise from the difficult chemical nature of membrane proteins, and the unclear relationship between their activity and their native environment. New approaches are therefore required to address these challenges. Recent developments in mass spectrometry have shown that it is possible to study membrane proteins in a solvent‐free environment and provide detailed insights into complex interactions, ligand binding and folding processes. Interestingly, not only detergent micelles but also lipid bilayer nanodiscs or bicelles can serve as a means for the gentle desolvation of membrane proteins in the gas phase. In this manner, as well as by direct addition of lipids, it is possible to study the effects of different membrane components on the structure and function of the protein components allowing us to add functional data to the least accessible part of the proteome.